Cross-border and foreign-affiliate sales of services: Evidence from German micro-data - Markus Kelle; Jörn Kleinert; Horst Raff; Farid Toubal (Kiel Institute for the World Economy (IfW), 2012)
We merge German balance-of-payments and foreign-affiliate-trade statistics to obtain data about trade in commercial services at the firm level. We use these data to study export market participation and the choice of export mode: cross-border versus foreign affiliate sales. We find that for firms in our sample productivity is both a statistically significant and economically important determinant of the export participation and export mode choice. We also identify the role of industry- and country-specific determinants.
Keywords: F12; F15; L13; 330; international trade; trade in services; supply modes; commercial presence; foreign direct investment; multinational enterprises; firm heterogeneity; Unternehmensdienstleistung; Internationaler Dienstleistungsverkehr; Ausländische Tochtergesellschaft; Firmeninterner Handel; Multinationales Unternehmen; Produktivität; Schätzung; Deutschland